L’arroganza di Prometeo. Dal poema agronomico di Spolverini nella Crestomazia poetica alla Ginestra - Diafani, Laura (Rivista Internazionale di Studi Leopardiani, 2021)
XVIII century’s georgic texts chosen by Leopardi in his poetic Crestomazia represent Nature controlled by human knowledge. In particular, some verses from Coltivazione del riso (1758) by Giovan Battista Spolverini’s debate an ecologic topic and introduce a subject which is satirized in Palinodia al marchese Gino Capponi but it is also fundamental in La ginestra o il fiore del deserto, that is the contemporary goundless arrogance and pride of the human being in front of Nature.